Recyclable high-barrier packaging film material and preparation method thereof
By adopting a three-layer packaging film material, using linear polyethylene particles, metallocene polyethylene, polyolefin elastomer and composite barrier agents, the existing film material has solved the problem of taking into account the recovery and barrier properties, and achieved high barrier, good recycling and anti-oxidation properties.
Patent Information
- Application Number
- CN202510315815.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-18
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2045-03-18
AI Technical Summary
Existing plastic packaging films are difficult to balance the environmental recyclability and barrier properties, especially in the food and medicine fields, and long-term storage needs are difficult to meet.
The packaging film material with a three-layer structure is adopted. The upper and lower layers are composed of linear polyethylene particles and metallocene polyethylene composite materials. The middle layer is added with polyolefin elastomer and composite barrier agents, including modified montmorillonite and microfibrous cellulose. Lignin acetate can also be added to improve antioxidant properties.
The high barrier properties and good recycling properties of the film are achieved, and the tensile, rubbing and oxidation resistance of the film is improved, which extends the service life and reduces environmental pollution.
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of packaging materials, and more specifically, to a recyclable high-barrier packaging film material and a preparation method thereof. Background Art
[0002] Packaging film is a means to reduce oxidation and contamination of packaged materials. It can wrap the packaged materials, isolate the packaged materials from the outside world, and reduce the contact of the packaged materials with oxygen and moisture, thereby improving the storage resistance and storage ease of the packaged materials. Packaging film materials are mostly plastic products with good processing performance and low cost, and are widely used in various fields.
[0003] However, plastic film materials are not easily degraded by the environment. If they are not recycled, they will cause great pollution to the environment. At the same time, the commonly used plastic film materials on the market often do not have sufficient barrier properties and cannot meet the long-term storage needs of certain special products, especially in the food and medicine fields. Although there are various means to improve the barrier properties of film materials, the barrier properties and recyclability of film materials cannot be achieved at the same time. Summary of the invention
[0004] In order to improve the barrier properties and recyclability of packaging film materials, the present application provides a recyclable high-barrier packaging film material and a preparation method thereof.
[0005] In a first aspect, the present application provides a recyclable high-barrier packaging film material, which adopts the following technical solution: A recyclable high-barrier packaging film material comprises an upper layer, a middle layer and a lower layer. The upper layer comprises the following raw materials in parts by weight: 40-55 parts of linear polyethylene particles and 35-45 parts of metallocene polyethylene; the middle layer comprises the following raw materials in parts by weight: 40-50 parts of linear polyethylene particles, 5-8 parts of polyolefin elastomer, and 1.2-1.8 parts of a composite barrier agent; and the lower layer comprises the following raw materials in parts by weight: 45-60 parts of linear polyethylene particles and 10-18 parts of metallocene polyethylene.
[0006] By adopting the above technical scheme, the upper layer, the middle layer and the lower layer are mainly composed of linear polyethylene particles, so that the polyethylene content of the film is ≥95%, which meets the requirements of recycling. At the same time, the upper layer and the lower layer use linear polyethylene and metallocene polyethylene in combination. The metallocene polyethylene has good miscibility and can effectively improve the tensile strength of the film, thereby ensuring the strength of the film. The middle layer is added with polyolefin elastomer, which can effectively improve the rubbing resistance of the film and help extend the service life of the film. At the same time, the composite barrier agent can enhance the barrier performance of the middle layer of the film, thereby improving the barrier performance of the film.
[0007] Preferably, the composite barrier comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of (1.95-2.13):(0.45-0.62).
[0008] By adopting the above technical solution, the modified montmorillonite has a higher specific surface area, which can block oxygen, making the diffusion path of oxygen complicated and the diffusion rate decreased, while the microfibrillated cellulose can be compounded with the modified montmorillonite to form an intercalated structure, further increasing the barrier effect of the composite barrier agent.
[0009] Preferably, the preparation method of the modified montmorillonite comprises the following steps: mixing anhydrous ethanol, water and a silane coupling agent, adjusting the pH to 4-5 with acetic acid, reacting at 50°C for 3 hours, adding sodium montmorillonite, stirring for 12 hours, ultrasonically dispersing for 1 hour, reacting at 80°C for 5 hours, cooling, centrifuging, washing and drying to obtain the modified montmorillonite.
[0010] By adopting the above technical solution and using a silane coupling agent to modify the sodium-based montmorillonite, the hydroxyl content on the surface of the modified montmorillonite can be effectively reduced, which is beneficial to improving the dispersibility of the modified montmorillonite and further improving the barrier properties of the film material.
[0011] Preferably, the mass ratio of the silane coupling agent to sodium-montmorillonite is (2.98-3.24):(3.89-4.51).
[0012] By adopting the above technical solution, the mass ratio of the silane coupling agent to the sodium-montmorillonite is controlled, which is beneficial to improving the modification effect of the silane coupling agent on the sodium-montmorillonite, so that the surface of the sodium-montmorillonite is epoxy-modified and its dispersibility is improved.
[0013] Preferably, acetic acid lignin is further added to the middle layer, and the amount of acetic acid lignin added is 1.38-2.61wt% of the linear polyethylene particles in the middle layer.
[0014] By adopting the above technical solution, acetic lignin has good antioxidant activity. Adding acetic lignin to the middle layer can effectively reduce the oxygen permeability of the middle layer, and at the same time can remove free radicals, thereby improving the antioxidant and oxygen barrier properties of the film material.
[0015] Preferably, the preparation method of acetic acid lignin comprises the following steps: crushing and drying the bamboo shoot shells, dispersing them in water, extracting them in a water bath at 95°C for 2h, adding them to an acetic acid solution, adding a hydrochloric acid solution, reacting them in an oil bath at 114°C for 80min, vacuum filtering, washing with acetic acid, washing with clean water, precipitating, centrifuging, separating, and freeze-drying to obtain acetic acid lignin.
[0016] By adopting the above technical scheme, lignin in bamboo shoot shells can be extracted to obtain acetic lignin, the extraction efficiency is high, and the obtained acetic lignin has good antioxidant properties.
[0017] Preferably, the amount of bamboo shoot shells added is 4.02-4.35wt% of the acetic acid solution.
[0018] By adopting the above technical solution, the amount of acetic acid solution and lignin is controlled, the extraction amount of acetic acid lignin is increased, and at the same time, the lignin and the fiber are not separated, thereby effectively improving the extraction rate of acetic acid lignin.
[0019] In a second aspect, the present application provides a method for preparing a recyclable high-barrier packaging film material, which adopts the following technical solution: A method for preparing a recyclable high-barrier packaging film material comprises the following steps: respectively mixing raw materials of an upper layer, a middle layer and a lower layer, and then co-extruding the three layers to prepare the film material.
[0020] By adopting the above technical solution, the prepared film material has good barrier properties and anti-oxidation properties, which is beneficial to the long-term storage of objects in the film material.
[0021] In summary, this application has the following beneficial effects: 1. Since the upper layer, middle layer and lower layer in the present application are mainly composed of linear polyethylene particles, the polyethylene content of the film material is ≥95%, which meets the requirements for recycling. At the same time, the upper layer and the lower layer use linear polyethylene and metallocene polyethylene in combination. Metallocene polyethylene has good miscibility and can effectively improve the tensile strength of the film material, thereby ensuring the strength of the film material. The middle layer is added with polyolefin elastomer, which can effectively improve the rubbing resistance of the film material and help extend the service life of the film material. At the same time, the composite barrier agent can enhance the barrier performance of the middle layer of the film material, thereby improving the barrier performance of the film material.
[0022] 2. The modified montmorillonite in the present application has a high specific surface area, which can block oxygen, making the diffusion path of oxygen complicated and the diffusion rate decreased, and the microfibrillated cellulose can be compounded with the modified montmorillonite to form an intercalated structure, further increasing the barrier effect of the composite barrier agent.
[0023] 3. In the present application, acetic lignin has good antioxidant activity. Adding acetic lignin to the middle layer can effectively reduce the oxygen permeability of the middle layer, and can also remove free radicals, thereby improving the antioxidant and oxygen barrier properties of the film material. DETAILED DESCRIPTION
[0024] The present application is further described in detail below with reference to the embodiments.
[0025] Preparation Examples 1-4 of Modified Montmorillonite
[0026] Preparation Example 1 The preparation method of modified montmorillonite comprises the following steps: 75 mL of anhydrous ethanol, 8 mL of water and 3 mL of silane coupling agent KH-560 are mixed, 10 wt% of acetic acid is used to adjust the pH value to 4, the mixture is reacted at 50 DEG C for 3 hours, sodium montmorillonite is added, the mass ratio of the silane coupling agent to the sodium montmorillonite is 2.98:3.89, the mixture is stirred for 12 hours, ultrasonically dispersed for 1 hour, the mixture is reacted at 80 DEG C for 5 hours, cooled, centrifuged, washed and dried to obtain the modified montmorillonite.
[0027] Preparation Example 2 The preparation method of modified montmorillonite comprises the following steps: 80 mL of anhydrous ethanol, 10 mL of water and 3.2 mL of silane coupling agent KH-560 are mixed, 10 wt% of acetic acid is used to adjust the pH to 5, the mixture is reacted at 50°C for 3 hours, sodium montmorillonite is added, the mass ratio of the silane coupling agent to the sodium montmorillonite is 3.24:4.51, the mixture is stirred for 12 hours, ultrasonically dispersed for 1 hour, the mixture is reacted at 80°C for 5 hours, cooled, centrifuged, washed and dried to obtain the modified montmorillonite.
[0028] Preparation Example 3 The difference between Preparation Example 3 and Preparation Example 1 is that the mass ratio of the silane coupling agent to the sodium-montmorillonite is 2.98:2.21.
[0029] Preparation Example 4 The difference between Preparation Example 4 and Preparation Example 1 is that the mass ratio of the silane coupling agent to the sodium-montmorillonite is 2.98:5.68.
[0030] Preparation Example 5-8 of Acetate Lignin
[0031] Preparation Example 5 The preparation method of acetic acid lignin comprises the following steps: crushing and drying bamboo shoot shells, dispersing them in water, extracting them in a water bath at 95°C for 2h, adding them into an 87wt% acetic acid solution, wherein the amount of bamboo shoot shells added is 4.02wt% of the acetic acid solution, adding a 4wt% hydrochloric acid solution, wherein the amount of HCl added is 6%, reacting them in an oil bath at 114°C for 80min, vacuum filtering, washing with acetic acid, washing with clean water, precipitating, centrifuging, separating, and freeze-drying to obtain acetic acid lignin.
[0032] Preparation Example 6 The preparation method of acetic acid lignin comprises the following steps: crushing and drying bamboo shoot shells, dispersing them in water, extracting them in a water bath at 95°C for 2h, adding them into a 90wt% acetic acid solution, wherein the amount of bamboo shoot shells added is 4.35wt% of the acetic acid solution, adding a 5wt% hydrochloric acid solution, wherein the amount of HCl added is 6%, reacting them in an oil bath at 114°C for 80min, vacuum filtering, washing with acetic acid, washing with clean water, precipitating, centrifuging, separating, and freeze-drying to obtain acetic acid lignin.
[0033] Preparation Example 7 The difference between Preparation Example 7 and Preparation Example 5 is that the amount of bamboo shoot shells added is 3.21 wt % of the acetic acid solution.
[0034] Preparation Example 8 The difference between Preparation Example 8 and Preparation Example 5 is that the amount of bamboo shoot shells added is 5.98 wt % of the acetic acid solution.
[0035] In this embodiment, the linear polyethylene particles are selected from LLDPE XP 7021ML, the metallocene polyethylene is selected from M8470, and the polyolefin elastomer is selected from Engage 8842.
[0036] Example 1 A recyclable high-barrier packaging film material comprises an upper layer, a middle layer and a lower layer, wherein the upper layer comprises the following raw materials in parts by weight: 40 kg of linear polyethylene particles and 35 kg of metallocene polyethylene; the middle layer comprises the following raw materials in parts by weight: 40 kg of linear polyethylene particles, 5 kg of polyolefin elastomer, and 1.2 kg of a composite barrier agent, wherein the composite barrier agent comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of 1.95:0.45, and the modified montmorillonite is the modified montmorillonite prepared in Preparation Example 1; the lower layer comprises the following raw materials in parts by weight: 45 kg of linear polyethylene particles and 10 kg of metallocene polyethylene.
[0037] The method for preparing the above-mentioned recyclable high-barrier packaging film material comprises the following steps: mixing the raw materials of the upper layer, the middle layer and the lower layer respectively, and then co-extruding the three layers to prepare the film material.
[0038] Example 2 A recyclable high-barrier packaging film material comprises an upper layer, a middle layer and a lower layer, wherein the upper layer comprises the following raw materials in parts by weight: 55 kg of linear polyethylene particles and 45 kg of metallocene polyethylene; the middle layer comprises the following raw materials in parts by weight: 50 kg of linear polyethylene particles, 8 kg of polyolefin elastomer, and 1.8 kg of a composite barrier agent, wherein the composite barrier agent comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of 2.13:0.62, and the modified montmorillonite is the modified montmorillonite obtained in Preparation Example 1; the lower layer comprises the following raw materials in parts by weight: 60 kg of linear polyethylene particles and 18 kg of metallocene polyethylene.
[0039] The method for preparing the above-mentioned recyclable high-barrier packaging film material comprises the following steps: mixing the raw materials of the upper layer, the middle layer and the lower layer respectively, and then co-extruding the three layers to prepare the film material.
[0040] Example 3 The difference between Example 3 and Example 1 is that the composite barrier comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of 1.95:0.23.
[0041] Example 4 The difference between Example 4 and Example 1 is that the composite barrier comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of 1.95:0.89.
[0042] Example 5 The difference between Example 5 and Example 1 is that the modified montmorillonite is the modified montmorillonite prepared in Preparation Example 3.
[0043] Example 6 The difference between Example 6 and Example 1 is that the modified montmorillonite is the modified montmorillonite prepared in Preparation Example 4.
[0044] Example 7 The difference between Example 7 and Example 1 is that acetic lignin is further added to the middle layer, and the amount of acetic lignin added is 1.38wt% of the linear polyethylene particles in the middle layer. The acetic lignin is the acetic lignin prepared in Preparation Example 5.
[0045] Example 8 The difference between Example 8 and Example 1 is that acetic lignin is further added to the middle layer, and the added amount of acetic lignin is 2.61wt% of the linear polyethylene particles in the middle layer. The acetic lignin is the acetic lignin prepared in Preparation Example 6.
[0046] Example 9 The difference between Example 9 and Example 7 is that the amount of acetic acid lignin added is 0.25wt% of the middle-layer linear polyethylene particles.
[0047] Example 10 The difference between Example 10 and Example 7 is that the amount of acetic acid lignin added is 3.98 wt % of the middle-layer linear polyethylene particles.
[0048] Embodiment 11 The difference between Example 11 and Example 7 is that the acetic lignin is the acetic lignin prepared in Preparation Example 7.
[0049] Example 12 The difference between Example 12 and Example 7 is that the acetic lignin is the acetic lignin prepared in Preparation Example 8.
[0050] Comparative Example 1 The difference between Comparative Example 1 and Example 1 is that no polyolefin elastomer is added to the middle layer.
[0051] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that no composite barrier is added to the middle layer.
[0052] Comparative Example 3 The difference between Comparative Example 3 and Example 1 is that an equal amount of modified montmorillonite is used instead of the composite barrier.
[0053] Comparative Example 4 The difference between Comparative Example 4 and Example 1 is that an equal amount of microfibrillated cellulose is used instead of the composite barrier agent.
[0054] Detection Methods
[0055] Films were prepared according to the raw materials and preparation methods of Examples 1-12 and Comparative Examples 1-4, and tested using a GDP-C gas permeometer according to GB / T 1038-2000 "Plastic Film and Sheet Gas Permeability Test Method - Pressure Difference Method", with the temperature set to 23°C and the relative humidity set to 50%. The film was cut into 3 parallel samples of appropriate sizes for testing, and the average value was calculated and recorded in Table 1. The test method for the rubbing resistance of flexible packaging materials in GB / T41347-2022 was used to record the number of pinholes after 8100 rubbings, and recorded in Table 1.
[0056] Table 1 Oxygen permeability and rubbing resistance of membranes project Oxygen permeability / cm³ / (m²·d·pa) Number of pinholes Example 1 0.43 2 Example 2 0.42 2 Example 3 0.65 2 Example 4 0.62 2 Example 5 0.49 2 Example 6 0.48 2 Example 7 0.37 2 Example 8 0.36 2 Example 9 0.47 2 Example 10 0.49 2 Embodiment 11 0.51 2 Example 12 0.50 2 Comparative Example 1 0.43 3 Comparative Example 2 0.95 2 Comparative Example 3 0.68 2 Comparative Example 4 0.67 2 According to Examples 1-2, Table 1 and Comparative Examples 1-2, it can be seen that the film material prepared in Examples 1-2 not only has a lower oxygen permeability, but also has good rubbing resistance. The upper and lower layers are composited with linear polyethylene and metallocene polyethylene. The metallocene polyethylene has good miscibility, so that the texture of the upper and lower layers is uniform. At the same time, the metallocene polyethylene has good tensile strength, which can effectively improve the strength of the upper and lower layers, thereby improving the strength of the film. Polyolefin elastomer is added to the middle layer, which can improve the flexibility and elasticity of the middle layer, thereby improving the rubbing resistance of the film. The composite barrier formed by the composite of modified montmorillonite and microfibrillated cellulose has a good barrier effect on oxygen, can reduce the oxygen permeability of the film, thereby improving the barrier performance of the film.
[0057] Compared with Example 1-2, Example 3-4 and Comparative Example 3-4 have improved oxygen permeability of the membrane, indicating that the barrier properties of the membranes prepared in Example 3-4 and Comparative Example 3-4 are reduced. Example 3-4 changes the mass ratio of modified montmorillonite to microfibrillated cellulose, and Comparative Example 3 only adds modified montmorillonite, and Comparative Example 4 only adds microfibrillated cellulose, indicating that the composite barrier agent formed by the composite of modified montmorillonite and microfibrillated cellulose has higher barrier properties, which is more effective than the single use of modified montmorillonite or microfibrillated cellulose. Modified montmorillonite has a higher specific surface area and can block oxygen, making the diffusion path of oxygen complicated and the diffusion rate reduced, while microfibrillated cellulose can be composited with modified montmorillonite to form an intercalated structure, which further increases the barrier effect of the composite barrier agent. The composite of the two according to the mass ratio can give full play to the synergistic effect, thereby effectively improving the barrier properties of the membrane.
[0058] Compared with Example 1-2, the oxygen permeability of the film material in Example 5-6 is improved, which means that the barrier performance of the film material prepared in Example 5-6 is reduced. When preparing the modified montmorillonite used in Example 5-6, the mass ratio of the silane coupling agent to the sodium montmorillonite was changed. The mass ratio of the silane coupling agent to the sodium montmorillonite affected the number of hydroxyl groups on the surface of the sodium montmorillonite. The silane coupling agent treatment can epoxy-modify the surface of the sodium montmorillonite, which is beneficial to improving its dispersion performance. The change in the mass ratio reduces the modification effect of the silane coupling agent on the surface of the sodium montmorillonite, thereby reducing the dispersibility of the modified montmorillonite and reducing the barrier effect of the composite barrier agent.
[0059] Compared with Examples 1-2, the oxygen permeability of the film material in Examples 7-8 decreases, indicating that the barrier performance of the film material prepared in Examples 7-8 is improved. In Examples 7-8, acetic lignin is added to the middle layer. Acetic lignin has good antioxidant activity. Adding acetic lignin to the middle layer can effectively reduce the oxygen permeability of the middle layer, and at the same time can scavenge free radicals, thereby improving the antioxidant and oxygen barrier properties of the film material. The addition of acetic lignin can effectively improve the antioxidant and oxygen barrier properties of the middle layer, thereby improving the barrier properties of the film material.
[0060] Compared with Examples 7-8, the oxygen permeability of the film material in Examples 9-10 is improved, indicating that the barrier performance of the film material prepared in Examples 9-10 is reduced. In Examples 9-10, the amount of acetic lignin added is changed. The amount of acetic lignin added is reduced, so that the enhancement of the barrier performance of the film material by acetic lignin is weakened, and the barrier performance of the film material is reduced. The amount of acetic lignin added is increased, and the acetic lignin is prone to agglomeration and uneven distribution, thereby reducing the barrier performance of the film material.
[0061] Compared with Examples 7-8, the oxygen permeability of the film materials in Examples 11-12 is improved, indicating that the barrier performance of the film materials prepared in Examples 11-12 is reduced. When preparing the acetic lignin in Examples 11-12, the amount of bamboo shoot shell added was changed. The increase in the amount of bamboo shoot shell added resulted in a decrease in the extracted acetic lignin, while the decrease in the amount of bamboo shoot shell added resulted in excessive acetic acid, which caused the lignin to separate from the fiber, and also reduced the extraction rate of acetic lignin.
[0062] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. A recyclable high-barrier packaging film material, characterized in that: It comprises an upper layer, a middle layer and a lower layer. The upper layer comprises the following raw materials in parts by weight: 40-55 parts of linear polyethylene particles and 35-45 parts of metallocene polyethylene; the middle layer comprises the following raw materials in parts by weight: 40-50 parts of linear polyethylene particles, 5-8 parts of polyolefin elastomer, and 1.2-1.8 parts of composite barrier agent; the lower layer comprises the following raw materials in parts by weight: 45-60 parts of linear polyethylene particles and 10-18 parts of metallocene polyethylene.
2. The recyclable high-barrier packaging film material according to claim 1, characterized in that: The composite barrier comprises modified montmorillonite and microfibrillated cellulose in a mass ratio of (1.95-2.13):(0.45-0.62).
3. The recyclable high-barrier packaging film material according to claim 2, characterized in that: The preparation method of the modified montmorillonite comprises the following steps: mixing anhydrous ethanol, water and a silane coupling agent, adjusting the pH to 4-5 with acetic acid, reacting at 50°C for 3h, adding sodium montmorillonite, stirring for 12h, ultrasonically dispersing for 1h, reacting at 80°C for 5h, cooling, centrifuging, washing and drying to obtain the modified montmorillonite.
4. The recyclable high-barrier packaging film material according to claim 3, characterized in that: The mass ratio of the silane coupling agent to the sodium-montmorillonite is (2.98-3.24):(3.89-4.51).
5. The recyclable high-barrier packaging film material according to claim 1, characterized in that: Acetate lignin is also added to the middle layer, and the amount of acetic lignin added is 1.38-2.61wt% of the linear polyethylene particles in the middle layer.
6. The recyclable high-barrier packaging film material according to claim 5, characterized in that: The preparation method of acetic acid lignin comprises the following steps: crushing and drying bamboo shoot shells, dispersing them in water, extracting them in a water bath at 95°C for 2h, adding them into an acetic acid solution, adding a hydrochloric acid solution, reacting them in an oil bath at 114°C for 80min, vacuum filtering, washing with acetic acid, washing with clean water, precipitating, centrifuging, separating, and freeze-drying to obtain acetic acid lignin.
7. The recyclable high-barrier packaging film material according to claim 6, characterized in that: The amount of bamboo shoot shells added is 4.02-4.35wt% of the acetic acid solution.
8. The method for preparing the recyclable high-barrier packaging film according to any one of claims 1 to 7, characterized in that: The following steps are involved: The raw materials of the upper layer, the middle layer and the lower layer are mixed separately, and then three layers are co-extruded to obtain the film material.
Citation Information
Patent Citations
Elastic label film
CN101049748A
Method for extracting lignin from bamboo shoot shells
CN109337092A
Montmorillonite modified cellulose high-barrier composite film and preparation method thereof
CN112694627A
Recyclable high-barrier packaging film and preparation method thereof
CN114474925A
Rainproof reflective film for truck and preparation method thereof
CN114619739A
Cited By
Rubbing-resistant film, high-barrier packaging bag and preparation method
CN120024085A